Composition, diversity, and value of ecological importance in Andean grassland ecosystems according to the altitudinal gradient in the Huacracocha micro-watershed, Peru - Yaranga, Raúl M. (2023)
Aims: determine the composition and floristic diversity, the similarity between sites based on the distribution of species in the altitudinal gradient, and determine the value of ecological importance, in Andean grassland ecosystems. Study Design: Original research. Place and Duration of Study: This study took place in the Huacracocha micro-watershed in the Central Highlands of Peru, during the rainy season (January - March 2022). Methodology: The agrostological evaluation points were determined taking into account twelve sites of interest were determined, located from the lowest part of the micro-watershed (4091.8 masl) to the part with the highest vegetation cover (4512.27 masl), the agrostological reading process at each evaluation site was carried out using the radial transect method with the line and intercept point technique. Results: We observed the presence of the presence of 78 vascular species, included in 51 genus and 21 families, was found. The dominance of certain species characterized the type of grassland vegetation, and at least 3 species determined the similarity between sites. The alpha diversity index was low, and the value of ecological importance ranged between 0.0062 and 0.2194. Conclusion: It was concluded that the Andean grassland ecosystems are constituted by a complex community of grasslands based on numerous floristic families, genus, and species, likewise, the dominance of species among the shared sites characterizes the vegetation type, and the diversity index and the IVI determine the complex structural characteristics with great biodiversity.